2005
DOI: 10.1590/s0101-60832005000100001
|View full text |Cite
|
Sign up to set email alerts
|

Diferenças entre fatores de risco para infecção pelo HIV em usuários de drogas injetáveis do Rio de Janeiro e Porto Alegre

Abstract: Pechansky, R.; Von Diemen, L.; Kessler, F.; Surratt, H.; Inciardi, J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Two studies targeting people who injected drugs in Rio de Janeiro in the 1990s found HIV-1 prevalence rates of 26.3% and 15.9% [ 15 , 31 ]. In the same period, higher rates of HIV-1 prevalence (65%) were also detected in a study conducted in Porto Alegre, Southern Brazil [ 31 ] and in two multicity studies in this key population at higher risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies targeting people who injected drugs in Rio de Janeiro in the 1990s found HIV-1 prevalence rates of 26.3% and 15.9% [ 15 , 31 ]. In the same period, higher rates of HIV-1 prevalence (65%) were also detected in a study conducted in Porto Alegre, Southern Brazil [ 31 ] and in two multicity studies in this key population at higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies targeting people who injected drugs in Rio de Janeiro in the 1990s found HIV-1 prevalence rates of 26.3% and 15.9% [ 15 , 31 ]. In the same period, higher rates of HIV-1 prevalence (65%) were also detected in a study conducted in Porto Alegre, Southern Brazil [ 31 ] and in two multicity studies in this key population at higher risk. The first one, AjUDE-Brasil I, conducted in 1998, in five Brazilian cities (São Paulo, Sorocaba, and São José do Rio Preto from the State of São Paulo; Itajaí (SC); and Porto Alegre, Rio Grande do Sul [RS]), and the second one, AjUDE-Brasil II, carried out in 2000–2001 in six cities (Salvador (BA); São José do Rio Preto (SP); Florianópolis and Itajaí (SC); Porto Alegre and Gravataí [RS]) found HIV-1 prevalences of 52.3% and 45.8%, respectively [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various international studies demonstrate that HIV infection among female and male IDUs are associated with distinct factors, predominantly heterosexual activity and the presence of recent sexually transmitted diseases (STDs) 4 , as well as syringe sharing and unprotected sexual contact with an-other IDUs 5 . Also in Brazil, a study 6 of 250 injection cocaine users showed greater prevalence of HIV among women, attributed to unprotected heterosexual sex with IDUs. On the other hand, among 2,994 women attended by the Anonymous Testing Service, it was found that low education, low family income, injection drug use, and clinical history of STDs are risk factors for HIV infection 7 .…”
Section: Introductionmentioning
confidence: 99%
“…O consumo de crack não só está relacionado às internações, como também é considerado como fator de risco para infecção pelo HIV e outras IST (AZEVEDO, BOTEGA & GUIMARAES, 2006). Artigos abordando as vulnerabilidades permeadas ao uso do crack identificam que, nos momentos de necessidade de consumo da droga, muitos usuários fazem sexo em troca de droga ou mesmo do dinheiro necessário para comprá-la, expondo-se ao risco às IST, gravidez indesejada, bem como violência sexual (BONI et al, 2005;AZEVEDO, BOTEGA & GUIMARAES, 2006;NUNES et al, 2007;MALTA et al, 2008;CARVALHO & SEIBEL, 2009;COSTA et al, 2012). ;GUIMARÃES, 2007;BRASIL, 2013a;SANTOS, et al, 2016;NEMES, et al, 2009), cujo enfrentamento exige políticas públicas mais abrangentes, robustas e capazes de articular atores e setores da sociedade.…”
Section: Plano De Análiseunclassified